1991
DOI: 10.1111/j.1439-0442.1991.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noradrenaline on Smooth Muscle Strips from the Reticular Groove of Adult Cattle

Abstract: Summary The effect of noradrenaline (NA) on smooth muscle strips from the reticular groove of adult cattle was studied. The mechanical activity of the muscle strips was recorded isometrically. Noradrenaline caused concentration dependent (1.1 · 10−6 ‐ 55 · 10−6mol/l) contractions of both the transversal muscle strips from the floor and the longitudinal muscle strips from the lips of the reticular groove. This excitatory effect of noradrenaline was antagonized by the α‐receptor antagonist prazosine (10−8 mol/1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…When a small increase in perfusion pressure elicited by 100 nmol nicotine returned to a base line, the second administration of 1 pmol ACh was injected immediately. The treatment with nicotine almost completely inhibited the vasoconstrictor response to ACh, but did not Figure 6 Vascular responses to acetylcholine (n = 6), noradrenaline (n = 3) and ATP (n = 4) before (0) and after (0) (Denac et al, 1991;Satake et al, 1992). Our present results provide further evidence in support of their observations.…”
Section: Vascular Responses To Nicotine and Achsupporting
confidence: 82%
“…When a small increase in perfusion pressure elicited by 100 nmol nicotine returned to a base line, the second administration of 1 pmol ACh was injected immediately. The treatment with nicotine almost completely inhibited the vasoconstrictor response to ACh, but did not Figure 6 Vascular responses to acetylcholine (n = 6), noradrenaline (n = 3) and ATP (n = 4) before (0) and after (0) (Denac et al, 1991;Satake et al, 1992). Our present results provide further evidence in support of their observations.…”
Section: Vascular Responses To Nicotine and Achsupporting
confidence: 82%
“…2003). Pharmaco‐physiological studies on the RG of calves have demonstrated that both nor‐adrenaline (Denac et al. 1991) and acetylcholine (Barahona et al.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few immunohistochemical studies referring to the ENS of the RG of bovines (Kitamura et al 1986(Kitamura et al , 1987Barahona et al 1997;Teixeira et al 1998) and sheep (Pfannkuche et al 2003). Pharmaco-physiological studies on the RG of calves have demonstrated that both nor-adrenaline (Denac et al 1991) and acetylcholine (Barahona et al 1997) play an essential role in the modulation of the activity and maintenance of muscle tone; in addition, a functional study involving esophageal groove strips revealed that NO plays a role in non-adrenergic non-cholinergic relaxation, which is significantly inhibited by incubation with L-NOARG, an inhibitor of NO synthesis (Barahona et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…O reflexo pode, inclusive, ser mantido ou provocado no animal adulto, como provaram ∅rskov et al (1970a), trabalhando com bovinos, e Mikhail et al (1988), com caprinos. Algumas substâncias, como sulfato de cobre (Brugere et al, 1987), bicarbonato de sódio (Carruthers et al, 1994), vasopressina (Brugere et al, 1987Van WeerenKaverling Buisman et al, 1990a) e noradrenalina (Denac et al, 1991) estimulam a ocorrência do reflexo, tanto em animais jovens como em adultos.…”
Section: Introductionunclassified